Quality of Institution and Slave Trade in Africa - Digale, Hared (Université d'Ottawa | University of Ottawa, 2015)
Nunn (2008) provided the first empirical evidence that linked slave trade to Africa's current poor economic development. In this paper, Nunn put forward a number of channels through which slave trade may have impacted on the current economic development in Africa. The channels he proposed include; mistrust, ethnic fractionalization, and state development. In this paper, I have looked at the possibility of the quality of institution as a channel through which slave trade has affected the continent's economy. Using Nunn's data and OLS estimation framework. I found no relationship between slave exports and each of the six indicators that I used to measure quality of institutions in Africa. I further used instrumental variables to mitigate the measurement errors of slave exports but still could not find a conclusive effect of slave trade on the quality of institutions in Africa.